2016
DOI: 10.1007/s10459-016-9727-0
|View full text |Cite
|
Sign up to set email alerts
|

Selecting for a sustainable workforce to meet the future healthcare needs of rural communities in Australia

Abstract: An undersupply of generalists doctors in rural communities globally led to widening participation (WP) initiatives to increase the proportion of rural origin medical students. In 2002 the Australian Government mandated that 25% of commencing Australian medical students be of rural origin. Meeting this target has largely been achieved through reduced standards of entry for rural relative to urban applicants. This initiative is based on the assumption that rural origin students will succeed during training, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
40
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 39 publications
1
40
0
1
Order By: Relevance
“…Conversely, Hay et al (2016) found that rural origin of students predicted intention to return to practice in rural settings, although not as a general practitioner (family physician) which is a specialty where greater numbers are needed in rural areas. As such, they conclude that rural origin widening participation initiative is only a part of the required solution to address rural health force undersupply.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…Conversely, Hay et al (2016) found that rural origin of students predicted intention to return to practice in rural settings, although not as a general practitioner (family physician) which is a specialty where greater numbers are needed in rural areas. As such, they conclude that rural origin widening participation initiative is only a part of the required solution to address rural health force undersupply.…”
Section: Discussionmentioning
confidence: 92%
“…On the contrary, they suggest that those students who manage to reach the qualifying standard for medical school despite the quality of the school they attended will, if anything, tend to perform better in medical school than students from high-performing schools due to their motivation and capacity to achieve ''against the odds''. Hay et al's (2016) paper also provides evidence that reducing selection cut points (academic achievement, UMAT, and interview) for rural applicants to Australian medical schools does not result in increased failure, or significantly impaired clinical performance during training.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…This binary approach may be increasingly important as schools seek to further diversify their student intake to better meet health and community needs. Schools may need to focus more on improving the accuracy and validity of selection tools close to the selection threshold mark rather than at the upper end of the scale 25 …”
Section: Discussionmentioning
confidence: 99%